MORPHOLOGICAL AND MOLECULAR CHARACTERIZATION OF POSTHARVEST FUNGAL PATHOGEN (Penicillium chrysogenum) IN POMEGRANATE FRUITS (Punica granatum L.) IN DUHOK PROVENCE- IRAQ - Dalal Sinjari; Shahad Abdullah; Jaladet Jubrael; Vian Musa (Mesopotamia Journal of Agriculture)
The research aimed to identify and characterize six samples of P. chrysogenum isolated from pomegranate fruits in Duhok City – Iraq. The study used morphological, internal transcribed spacer (ITS) region anitsd PCR-RFLP markers. The morphological examination revealed consistent characteristics across all six samples, indicating their classification as P. chrysogenum. The macroscopic features showed dense, blue-green colonies with a velvety texture, revealing brush-like conidiophores and distinctive conidia structures. Molecular analysis of the ITS region showed an approximately 600bp band that confirmed the morphological identification, providing additional support for the presence of P. chrysogenum in the pomegranate samples. The obtained sequences using 28S rRNA partial gene of 1200bp showed a high degree of similarity with known P. chrysogenum reference sequences, further validating the identification. Furthermore, the enzymes Rsa I, Hae III, and Alu I were chosen to study the restriction site amplification of the affected ITS region of all examined P. chrysogenum. The results showed significant identical amplified bands among the studied isolates. This study may pave the way for the distribution of P. chrysogenum pathogens in Duhok City and highlights the importance of integrating molecular and morphological techniques for accurate identification.